Advance power converter design for hybrid AC/DC Microgrids - Su, Wuxin (Nanyang Technological University, 2020)
Energy sustainability and smart grid technology are some of the most discussed topics in the 21st century. As countries continue to develop, their energy consumption soars exponentially. The most obvious example is in developing countries like China and India, their energy demands are increasing rapidly throughout the years. This is a huge issue to energy sustainability and global environmental issues because traditionally coal and natural gases had to be burnt to generate electricity and the output of the burning are mostly greenhouse gases that cause harmful effects to the environment. Furthermore, these natural resources are not unlimited, and they take millions of years to form. This raised a concern over energy sustainability as the earth may not have enough to generate electricity in the long run. Although there are still natural resources sites on earth to be found, researchers had been investing a great amount of time and money into discovering and harvesting renewable energy resources and how to integrate these resources management systems into a smart grid. The smart grid integrates all the different renewable energy systems with power grids and enable the management of energy demands as well as usage using smart-recording and measuring systems. Renewable resources mainly come in the form of wind, solar, hydro and geothermal energy. With the most popular ones being the wind and solar, most of the new renewable installations include onshore and offshore wind/solar photovoltaic farms. The challenges with harvesting solar and wind energy come in a form of energy quality. Take wind turbine generators for example. They are very large and costly to construct. The engineering behind wind turbine designs and generations are both complicated and time-consuming. Internally, the wind turbine system needs a three-phase generator to gather enough mechanical torque from the turbine spins to generate electrical energy. However, the wind speed or the solar irradiance (energy from the sun) changes throughout the days and seasons, it causes the generator to output variable voltages and frequencies, but most loads operates at a fixed voltage and frequency and the output cannot be directly supplied to the load. It is, therefore, a need for the voltage and current to go through conversion and stabilization stages which result in the inclusion of power converters. The solution here can be applied for wind turbine generation, as the converted energy will go through two-stage conversion by rectifiers, dc-link, and inverters. This power converter uses semi-conductor switching devices such as a diode, IGBT and MOSFET, with the right sensors and control strategies built to control these switches. This generated electricity is voltage and frequency controlled and is more suitable to be used by typical loads. It is also safer for the generator output to be grid-connected when it is controlled according to specifications. In this report, several energy conversion techniques will be discussed. The main objective and scope of the project will also be shown in this report, while showing the reader how converter systems can be designed more effectively with smaller rated capacitive components.